2012
DOI: 10.1016/j.jval.2012.08.1462
|View full text |Cite
|
Sign up to set email alerts
|

PUK24 Pharmacoeconomic Aspects of Use of Erythropoietin Drugs in Patients on Hemodialysis in Ukraine

Abstract: OBJECTIVES: Kaplan-Meier (KM) curves are commonly used to report time-toevent outcomes like overall survival (OS) and progression-free survival. For studies not explicitly reporting hazard ratio (HR) and confidence intervals (CI), KM curves can be utilised to estimate these summary statistics for conducting a meta-analysis. Here, we validate the method proposed by Parmar and colleagues for estimating HR (95%CI) by reading the KM curves. METHODS: Ten randomised controlled trials reporting HR (95%CI) and the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Unfortunately, it was not possible to evaluate the methodology of both previous publications and there concordance with international guidelines for CEA studies [ 19 ]. Considering only the cost of treatment; 3 cost-minimisation studies reported as meeting abstracts confirm our finding of cost saving after switch to CERA from another short acting EPO; Bezditko et al [ 20 ] estimated the cost reduction about 5–35%, based on decision tree analysis. In his pharmacoeconomic evaluation of maintenance treatment of anaemia, in Ukrainians haemodialysis patients, the average costs of CERA treatment per patient on haemodialysis were $173/week (intravenous route of administration) and $130/week (subcutaneous route of administration) and average costs for using the shorter-acting EpoB drugs were $267–194/week and $133–182/week, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Unfortunately, it was not possible to evaluate the methodology of both previous publications and there concordance with international guidelines for CEA studies [ 19 ]. Considering only the cost of treatment; 3 cost-minimisation studies reported as meeting abstracts confirm our finding of cost saving after switch to CERA from another short acting EPO; Bezditko et al [ 20 ] estimated the cost reduction about 5–35%, based on decision tree analysis. In his pharmacoeconomic evaluation of maintenance treatment of anaemia, in Ukrainians haemodialysis patients, the average costs of CERA treatment per patient on haemodialysis were $173/week (intravenous route of administration) and $130/week (subcutaneous route of administration) and average costs for using the shorter-acting EpoB drugs were $267–194/week and $133–182/week, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the hospital stay of treated patients due to Hb variations was reduced by 37% 42. For the Ukrainian dialysis population, estimated cost savings were 5%–35%, depending on the route of administration 43. Kawalec et al44 performed a CMA from the perspective of the public payer for predialysis patients and found a cost savings of €262.4/patient over a 2-year horizon compared to treatment with DA.…”
Section: Resultsmentioning
confidence: 99%
“… 42 For the Ukrainian dialysis population, estimated cost savings were 5%–35%, depending on the route of administration. 43 Kawalec et al 44 performed a CMA from the perspective of the public payer for predialysis patients and found a cost savings of €262.4/patient over a 2-year horizon compared to treatment with DA. Finally, assuming that CERA achieves a market share of 40%, Walsh et al 45 calculated a possible ESA budget reduction by 15% in five EU countries based on a United Kingdom budget impact model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation